Unsettling Assumptions : Tradition, Gender, Drag - Greenhill, Pauline; Tye, Diane, 1957- (Book collections on Project MUSE., 2014)
"In Unsettling Assumptions, editors Pauline Greenhill and Diane Tye link gender studies with traditional and popular culture studies to examine how tradition and gender can intersect to unsettle assumptions about culture and its study. Contributors explore the intersections of traditional expressive culture and sex/gender systems by challenging their conventional constructions, using sex/gender as a lens to question, investigate, or upset concepts like family, ethics, and authenticity. Individual essays consider myriad topics such as Thanksgiving turkeys, rockabilly and bar fights, Chinese tales of female ghosts, selkie stories, a noisy Mennonite New Year's celebration, the Distaff Gospels, Kentucky tobacco farmers, international adoptions, and more. In Unsettling Assumptions, expressive culture emerges as fundamental both to our sense of belonging to a family, an occupation, or friendship group and, most notably, to identity performativity. Within larger contexts, these works offer a better understanding of cultural attitudes like misogyny, homophobia, and racism as well as the construction and negotiation of power"--